Analysis of fluidized bed and inclined bed drying of paddy for Malaysia conditions - Sarker, Md. Sazzat Hossain (2014)
Industrial paddy drying is very important in Malaysia in terms of rice milling quality and energy consumption. This demands that drying conditions must be used that ensure the best quality rice and consume minimum energy. Less satisfactory operation of fluidized bed drying scheme imported from Thailand for the selected drying complexes of Padiberas Nasional Berhad (BERNAS) warranted further investigation. Besides, alternative industrial drying methods practiced in the complexes of BERNAS produce different quality milled rice that needed to be assessed to promote efficient operation. Computer simulation of industrial fluidized bed paddy drying and field investigation on industrial operation of existing single stage paddy drying using inclined bed dryer (IBD) and two stage paddy drying using fluidized bed dryer follwed by IBD were carried out to evaluate the present performances and to find out the possible ways of improving of the drying operations. Systematic and simplified approaches have been developed for evaluating the comparative performances of the industrial paddy drying systems in terms of drying behavior, quality of rice and energy consumption. The effect of drying methods on mechanical properties of rice dried with industrial methods was also investigated. In addition, energy and exergy analysis of industrial fluidized bed paddy drying was undertaken to determine the type and magnitude of exergy losses during high temperature (>100 oC) drying process. Simulation results indicated that the dryer gives better performance in terms of increased throughput capacity for drying of low initial moisture content (<30%db) paddy than drying of high moisture content paddy; the dryer could be operated up to almost double than its existing operating capacity (8.5 t/h), while high mc (>35 % db) hindered the capacity to be at or below 7.75 t/h even if higher temperature of 160 oC was used for reducing paddy moisture to desired outlet moisture of 24-25% (db). Based on field investigation, the FBDs dryers were found to be operated at lower throughput capacity (less than 50% of their design capacity) that caused higher specific energy consumption. The FBD of the complex of Simpang Empat, Perlis and Bukit Besar, Kedah were found to be operated at 7.75 to 9.5 t/h and 8.5 to 10.36 t/h throughput capacities, respectively where the maximum design capacities of these dryers were 25 t/h and 22 t/h, respectively. The comparative results of overall analysis between two stage and single stage paddy drying revealed that two-stage drying was still more suitable than single stage drying as it could reduce total process time up to 24.5% which ultimately led to raise the daily capacity of the drying complex while head rice yield (HRY) was found to be maintained between 44.5 to 52.5 % depending on seasons. In terms of specific energy consumption, the single and two stage drying consumed 5.07 to 6.38 MJ/kg of water evaporation and 5.95 to 8.02 MJ/kg of water evaporation, respectively. On the other hand, the single stage paddy drying using comparatively lower temperature of 35-39oC and two stage drying with FBD at 120 oC as first stage and followed by IBD at 35-39 oC as second stage yielded 2-3.6% higher HRY than paddy dried by single stage with IBD using comparatively higher temperature of 40-44 oC while the whiteness and milling recovery were comparable. The specific electrical energy consumption in kWh to dry each ton of fresh paddy ranged from 16.19 to 22.07 and 21.37 to 30.69 by single stage and two stage, respectively. The specific thermal energy consumption varied between 787.22 to 1015.32 MJ/t and 666.81 to 1083.42 MJ/t, respectively. The energy analysis also showed that the electrical energy up to 47% and thermal energy up to 27% could be saved, if paddy is dried by single stage drying with IBD at 40-44 oC but quality could not be maintained. The results on comparative analysis on product quality of rice dried by IBDs of two complexes indicated that HRY was significantly different at P ≤0.05 from one complex to another. In reducing paddy moisture from 22-23% wb down to around 12.5 % wb, the comparative milling results indicated that IBDs of Bukit Besar complex yielded 1-4% higher HRY for paddy dried at 38-39 oC than that of Simpang Empat complex where paddy was dried using 41-42 oC in the meantime milling recovery and whiteness were comparable at acceptable milling degree and transparency. The energy and exergy analysis results have shown that energy utilization ratio (EUR) increased and exergy efficiency decreased with increased drying air temperature and paddy initial moisture content. Meanwhile, EUR and exergy efficiency were found to be varied between 5.24 to 13.38 % and 41.30 to 58.14%, respectively. Exergy efficiency can be increased through providing sufficient insulation on dryer body and recycling the exhaust air which might need to further confirm for its economic viability. Overall investigation revealed that improper selection of drying air temperature for variable moist and impurity paddy lowered the performances of FBD. Simulation results and drying operation conducted at industry site revealed that the performance of the dryer in terms of increased drying capacity can be improved by altering the operating temperature based on simulation values. Paddy should be dried with IBD using temperature of 35-39 oC both in single stage drying and second stage drying after fluidized bed drying to obtain 1-4 % higher HRY.